1996
DOI: 10.1002/eej.4391170403
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of power system stability by on‐off discrete control of series capacitors

Abstract: Application ofcontrolled series capacitors with antiparallel thyristor combination across the capacitor segment is one of the new and promising countermeasures for enhancement of power system stability. The line reactance can be directly controlled by the controlled series capacitors, hence, it is very effective to apply the capacitors for damping power system disturbances.In this paper, we describe the following.(1) The design method of control system for the segmented series capacitors with thyristor switche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 2 publications
(1 reference statement)
0
7
0
Order By: Relevance
“…The system is called onoff discrete control. The authors have already shown that the improvement of system stability by onoff discrete control is the same as that of the continuous capacitance control [8].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…The system is called onoff discrete control. The authors have already shown that the improvement of system stability by onoff discrete control is the same as that of the continuous capacitance control [8].…”
Section: Introductionmentioning
confidence: 90%
“…8, there is a danger that SSR may occurs so long as the power system contains the series capacitor. Although the generation mechanism is the same, the probability of torsional oscillation of the shaft and SSR is expected to be higher than in the case of a series capacitor with fixed capacitance for the following two reasons.…”
Section: Generation Mechanism Of Ssr In Series-capacitor Compensated mentioning
confidence: 99%
See 2 more Smart Citations
“…Table 5 shows the angles of the first and second waves, swing periods, and damping time constants relative to the internal phase-difference angle of the generator. Here, the swing period is determined from the peaks of the first and second waves and the damping time constant is calculated from the following equation [8]:…”
Section: Step Change Of Tcsc Firing Anglementioning
confidence: 99%